The reliability and validity of superb microvascular imaging as a potential disease activity marker in rheumatoid arthritis - Kurtulus Ozturk, Esin; Ozturk, Saffet; Kelesoglu Dincer, Ayse Bahar (Ultraschall in der Medizin - European Journal of Ultrasound, 2025)
Rheumatoid arthritis (RA) is a systemic autoimmune disease of unknown etiology that causes progressive and destructive inflammation in the joints. Superb microvascular imaging (SMI) is a new ultrasound technique that allows visualization of slow blood flow in synovitis. This study aimed to report on the clinical value and utility of the SMI technique and its grading for monitoring RA by determining the correlation with clinical disease activity scores (DAS 28) and power Doppler ultrasound (PDUS).All RA patients with clinically apparent synovitis were assessed using DAS 28. Synovitis was investigated with PDUS and SMI and each joint was graded semi-quantitatively. All assessments were carried out at baseline and repeated at least at the 4-month follow-up. Correlations between scores were investigated using Spearman’s correlation.60 RA patients with 552 affected joints were recruited. Clinical and sonographic scores were significantly improved at follow-up (p<0.001). SMI showed significantly more joint count and flow signal scores than clinical examination and PDUS. Moderate correlations were found between the SMI score and clinical scores (p<0.001, 0.586 for SMI score vs. DAS 28-CRP, p=0.001, 0.432 for SMI vs. DAS 28-ESR). There were also stronger correlations between the SMI score and PDUS score at both baseline and follow-up (p<0.001, r = 0.817, 0.842 respectively).SMI provides greater utility and ability to detect synovial vascularity and to monitor disease activity than PDUS. A new activity scoring system based on SMI and clinical objective findings is required to improve reliability and validity.
Keywords: Superb microvascular imaging; synovitis; power Doppler ultrasound; Rheumatoid arthritis